Clinical value of hemoglobin, albumin, lymphocyte, and platelet indexes in predicting lymph node metastasis and recurrence of endometrial cancer: a retrospective study - Xiong,Ying; Yong,Yuanyuan; Wang,Yanhua (PeerJ, 2023)
Objective To study the clinical importance of hemoglobin, albumin, lymphocyte, and platelet (HALP) indexes in predicting lymph node metastasis and recurrence of endometrial cancer. Methods From July 2016 to July 2020, 158 patients suffering from endometrial cancer who visited the gynecology department of General Hospital of Ningxia Medical University from were collected. Employing the X-Tiles program, the ideal HALP cut-off value was established, and the patients were separated into low and high HALP groups. Univariate and multivariate analysis were used to determine the relationship between HALP score and lymph node metastasis and recurrence of endometrial cancer. Results The optimal cut-off value of HALP score was established to be 22.2 using X-Tiles software, and the patients were separated into high HALP group (HALP score > 22.2, with 43 cases) and low HALP group (HALP score ≤ 22.2, 115 cases). Endometrial cancer patients’ HALP scores were strongly connected with differentiation, the degree of myometrial invasion, and lymph node metastasis (P < 0.05), although not with age, menopausal status, or stage (P > 0.05). Multivariate logistic regression analysis revealed that the HALP score (OR = 2.087) was the influencing factor for lymph node metastasis (P < 0.05). The ROC curve suggested that the AUC of HALP score in predicting lymph node metastasis was 0.871, which had high diagnostic value. When compared to patients without recurrence, HALP scores of patients with recurrence were considerably lower (P < 0.05). Multivariate logistic regression analysis showed that HALP score (OR = 2.216) was the influencing factor for the occurrence of lymph node metastasis (P < 0.05). The ROC curve suggested that the AUC of HALP score in predicting relapse was 0.855, with high diagnostic value. Conclusion The HALP score shows good predictive performance in predicting lymph node metastasis and recurrence of endometrial cancer, and has high clinical value, which helps in improving the accuracy and effectiveness of clinical diagnosis and prognosis research.
Keywords: Hemoglobin; Albumin; Lymphocyte; Platelet index; Endometrial cancer; Lymph node metastasis; Recurrence; Clinical value